Light‐Induced Ammonia Generation over Defective Carbon Nitride Modified with Pyrite. Issue 43 (20th September 2022) - Zander, Judith; Timm, Jana; Weiss, Morten; Marschall, Roland
Abstract: Photocatalytic nitrogen fixation under ambient conditions is currently widely explored in an attempt to develop a sustainable alternative for the Haber–Bosch process. In this work, defect‐rich carbon nitride, one of the most investigated photocatalysts reported in literature for ammonia generation, is combined with earth‐abundant and bioinspired FeS2 to improve the activity for ammonia production. By this combination, an activity enhancement of ≈400% compared to unmodified carbon nitride is achieved. The optimal FeS2 loading is established to be 1 wt%, with ammonia yields of up to 800 µg L −1 after irradiation for 7 h. By detailed material characterization of the electronic and material properties of the composites before and after the photocatalytic reaction, it is revealed that NH3 generation occurs not photocatalytically from N2, but via a light‐induced reduction of N–CN groups adjacent to nitrogen vacancies in the structure of defect‐rich carbon nitride. FeS2 acts similar to a cocatalyst, enhancing the ammonia yield by π‐back‐donation from Fe‐centers to the imine nitrogen of the defect‐rich carbon nitride, thereby activating the structure and boosting the ammonia generation from cyano groups. Abstract : Two earth‐abundant materials namely carbon nitride and pyrite are combined to generate ammonia under sunlight irradiation. It is revealed that ammonia generation with defective carbon nitride is based on light‐induced reduction of N–CN groups adjacent to nitrogen vacancies in the structure of defect‐rich carbon nitride.